2011
DOI: 10.1002/hep.24605
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bilirubin and sera from jaundiced patients on osteoblasts: Contribution to the development of osteoporosis in liver diseases

Abstract: Low bone formation is considered to be the main feature in osteoporosis associated with cholestatic and end-stage liver diseases, although the consequences of retained substances in chronic cholestasis on bone cells have scarcely been studied. Therefore, we analyzed the effects of bilirubin and serum from jaundiced patients on viability, differentiation, mineralization, and gene expression in the cells involved in bone formation. The experiments were performed in human primary osteoblasts and SAOS-2 human oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 27 publications
8
73
1
Order By: Relevance
“…Since the cardiac jaundiced sera possess higher concentration of HGF, we assume that 5% sera induced hepatic differentiation of hMSCs with no significant effect on cell viability. Although, 10% sera also contain higher concentration of HGF, its anti-apoptotic and anti-necrotic effects would have been suppressed by the higher concentration of bilirubin and bile acids [52], [53]. Nevertheless, high serum level of HGF released from damaged heart/liver in such cases could effectively potentiate hepatic induction, comparable to that of known recombinant hepatogenic factors [20][22].…”
Section: Discussionmentioning
confidence: 99%
“…Since the cardiac jaundiced sera possess higher concentration of HGF, we assume that 5% sera induced hepatic differentiation of hMSCs with no significant effect on cell viability. Although, 10% sera also contain higher concentration of HGF, its anti-apoptotic and anti-necrotic effects would have been suppressed by the higher concentration of bilirubin and bile acids [52], [53]. Nevertheless, high serum level of HGF released from damaged heart/liver in such cases could effectively potentiate hepatic induction, comparable to that of known recombinant hepatogenic factors [20][22].…”
Section: Discussionmentioning
confidence: 99%
“…AIH may significantly contribute to BRONJ development in case of poor hepatic synthetic function, as high unconjugated and conjugated bilirubin levels are associated with decreased osteoblast viability and increased osteoclastogenesis [6]. The latter effect may be neutralized by potent BP agents, thus critically interfering with bone remodelling in the jaw.…”
Section: Discussionmentioning
confidence: 99%
“…These include prolonged corticosteroid exposure and, because of impaired synthetic hepatic function, high unconjugated bilirubin and impaired conversion of vitamin D to 25-hydroxy vitamin D [5, 6]. For this reason, bisphosphonate (BP) treatment is widely used in these patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…We speculate that a potential reason for the discrepancy between results is the differences in the study populations. Ruiz-Gaspa et al [23] reported that bilirubin inhibits bone formation and that a high bilirubin level leads to osteoporosis in end-stage liver disease. As valve calcification is an ectopic mineralization and has similar mechanisms to bone formation [7,9], we speculate that bilirubin could not prevent the formation of valve calcification; however, a positive relationship between a higher bilirubin level and valve calcification might indicate a compensatory anticalcification effect of bilirubin.…”
Section: Discussionmentioning
confidence: 99%